Thermoplastic vulcanized rubber material and preparation method thereof

By using modified polyhedral oligosilsesquioxane and its derivatives as flame retardant synergists in thermoplastic vulcanized rubber materials, combined with phosphorus and nitrogen flame retardants, the problem of poor compatibility of TPV materials and flame retardant is solved, and high flame retardant and good mechanical properties are achieved.

CN119752054APending Publication Date: 2025-04-04SHENZHEN WOER HEAT SHRINKABLE MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993229.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing thermoplastic vulcanized rubber materials (TPVs) are flammable during processing, and existing flame retardants have poor compatibility with the matrix, resulting in poor flame retardant effect.

Method used

Modified polyhedral oligosilsesquioxane and its derivatives are used as flame retardant synergists, combined with phosphorus and nitrogen flame retardants, and by modifying the boron element, a ring structure with a carbon-hydrogen ratio greater than 1 in the POSS flame retardant synergist, and a carbon layer, a ceramic barrier layer and a protective film are formed to improve the flame retardant performance.

Benefits of technology

It significantly improves the flame retardant performance of TPV materials, reduces the amount of flame retardant, and improves the mechanical properties of the materials, achieving high flame retardancy and good processing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752054A_ABST
    Figure CN119752054A_ABST
Patent Text Reader

Abstract

The invention discloses a thermoplastic vulcanized rubber material which comprises ethylene propylene diene monomer, polypropylene, a phosphorus flame retardant, a nitrogen flame retardant, modified polyhedral oligomeric silsesquioxane, a derivative flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and a cross-linking agent. The modified polyhedral oligomeric silsesquioxane and the derivative flame-retardant synergist thereof contain boron, an annular structure R2 with the carbon hydrogen ratio larger than 1 and two inorganic silicon cage cores, and the structures form a carbon layer, a ceramic barrier layer, a protective film or a heat-insulation coke layer and other protective layers in the combustion process, so that the anti-dripping effect is greatly improved, and meanwhile, the anti-dripping effect is greatly improved. Heat and oxygen transfer is isolated, combustible gas release is reduced, and the flame retardant property of the material is remarkably improved under the combined action of multiple mechanisms. Furthermore, the flame-retardant synergist of the modified polyhedral oligomeric silsesquioxane and the derivative of the modified polyhedral oligomeric silsesquioxane is matched with a phosphorus-based flame retardant for providing an acid source and a nitrogen-based flame retardant for providing a gas source to realize synergistic flame retardance, so that the flame-retardant property and the mechanical property of the thermoplastic vulcanized rubber material are improved while the consumption of the flame retardants is reduced. The thermoplastic vulcanized rubber material provided by the invention is excellent in flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a thermoplastic vulcanized rubber material. Background Art

[0002] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0003] Thermoplastic vulcanizate (TPV) is a thermoplastic elastomer prepared by dispersing ethylene propylene diene monomer (EPDM) into polypropylene (PP) material by dynamic vulcanization. It has both the high toughness of rubber and the plasticity of plastic and is widely used in the automotive, home appliance, cable and other industries. Existing TPV materials are generally flammable because a large amount of softening oil is added to the rubber during the processing. Existing flame-retardant TPVs are made by adding halogenated or halogen-free flame retardants to TPV materials. However, both halogenated and halogen-free flame retardants have poor compatibility with the TPV matrix. The flame retardant effect is poor at low addition amounts, and the performance is significantly reduced at high addition amounts. There is also a risk of precipitation, which affects the appearance of the product. Therefore, it is very necessary to develop a highly flame-retardant TPV material. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a thermoplastic vulcanized rubber material, aiming to solve the problem of poor flame retardancy of current TPV materials.

[0005] The above object of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a thermoplastic vulcanized rubber material, wherein the raw materials of the thermoplastic vulcanized rubber material, measured in parts by weight, include:

[0007] 50-70 parts of EPDM rubber,

[0008] Polypropylene 5-30 parts

[0009] Phosphorus flame retardant 20-40 parts,

[0010] 20-40 parts of nitrogen flame retardant,

[0011] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0012] Crosslinking agent 0.5-4 parts,

[0013] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0014]

[0015] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0016] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0017] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;

[0018] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

[0019] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0020]

[0021] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.

[0022] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:

[0023] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;

[0024] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0025] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0026] In some embodiments of the present invention, the raw materials of the thermoplastic vulcanized rubber material include, by weight:

[0027] 50-70 parts of EPDM rubber,

[0028] Polypropylene 10-30 parts

[0029] Phosphorus flame retardant 20-30 parts,

[0030] 20-30 parts of nitrogen flame retardant,

[0031] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0032] Cross-linking agent 0.5-4 parts.

[0033] In some embodiments of the present invention, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide;

[0034] And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

[0035] In some embodiments of the present invention, the raw materials of the thermoplastic vulcanized rubber material also include at least one of a plasticizer, a lubricant, an antioxidant, a toughening agent, a compatibilizer, and a filler; wherein the raw materials are calculated in parts by weight, the plasticizer is 20-40 parts, the lubricant is 0.2-1 parts, the antioxidant is 0.5-2 parts, the toughening agent is 5-10 parts, the compatibilizer is 5-10 parts, and the filler is 5-10 parts.

[0036] In a second aspect of the present invention, there is provided a method for preparing the above-mentioned thermoplastic vulcanized rubber material, comprising the following steps:

[0037] The raw materials, including EPDM rubber, polypropylene, phosphorus-based flame retardant, nitrogen-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, are mixed in an internal mixer according to weight to form a colloid, and the colloid is cooled and crushed to obtain crushed rubber blocks;

[0038] The broken rubber blocks and the cross-linking agent are mixed uniformly, melt-blended in an extruder, dynamically vulcanized, extruded and water-cooled to obtain granular material, namely the thermoplastic vulcanized rubber material.

[0039] In some embodiments of the present invention, the raw material further comprises at least one of a plasticizer, a lubricant, an antioxidant, a toughening agent, a compatibilizer, and a filler;

[0040] And / or, the processing temperature of each temperature zone of the extruder is: 90-100°C in zone 1, 160-180°C in zone 2, 190-200°C in zone 3, 190-220°C in zone 4, 190-220°C in zone 5, 190-220°C in zone 6, 190-220°C in zone 7, 190-220°C in zone 8, 180-200°C in zone 9, 180-200°C in zone 10, 200-210°C in zone 11, 200-210°C in die head, 400-600r / min in main engine speed, and 30-60r / min in feeding speed.

[0041] The thermoplastic vulcanized rubber material of the invention comprises ethylene propylene diene monomer rubber, polypropylene, phosphorus-based flame retardant, nitrogen-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, and crosslinking agent. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source and the nitrogen flame retardant providing the gas source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant properties and mechanical properties of the thermoplastic vulcanized rubber material. The thermoplastic vulcanized rubber material provided by the present invention has excellent flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;

[0043] Figure 2 This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0045] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.

[0046] Polyhedral oligomeric silsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.

[0047] Thermoplastic vulcanizate (TPV) is a thermoplastic elastomer prepared by dispersing ethylene propylene diene monomer (EPDM) into polypropylene (PP) material by dynamic vulcanization. It has both the high toughness of rubber and the plasticity of plastic and is widely used in the automotive, home appliance, cable and other industries. Existing TPV materials are generally flammable because a large amount of softening oil is added to the rubber during the processing. Existing flame-retardant TPVs are made by adding halogenated or halogen-free flame retardants to TPV materials. However, both halogenated and halogen-free flame retardants have poor compatibility with the TPV matrix. The flame retardant effect is poor at low addition amounts, and the performance is significantly reduced at high addition amounts. There is also a risk of precipitation, which affects the appearance of the product. Therefore, it is very necessary to develop a highly flame-retardant TPV material.

[0048] In order to solve the above problems, the first aspect of the present invention provides a thermoplastic vulcanized rubber material. The raw materials of the thermoplastic vulcanized rubber material, measured by weight, include:

[0049] 50-70 parts of EPDM rubber,

[0050] Polypropylene 5-30 parts

[0051] Phosphorus flame retardant 20-40 parts,

[0052] 20-40 parts of nitrogen flame retardant,

[0053] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0054] Crosslinking agent 0.5-4 parts,

[0055] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:

[0056]

[0057] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;

[0058] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

[0059] It can be understood that the EPDM rubber is any number between 50-70 parts, such as 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, etc.; the polypropylene is any number between 5-30 parts, such as 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, etc.; the phosphorus-based flame retardant is any number between 20-40 parts, such as 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, etc.; the nitrogen-based flame retardant is any number between 20 parts, 25 parts, 30 parts, 40 parts, etc. The amount of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is any amount between 2-15 parts, such as 30 parts, 35 parts, 40 parts, etc.; the amount of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is any amount between 2-15 parts, such as 2 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, etc.; the amount of the crosslinking agent is any amount between 0.5-4 parts, such as 0.5 parts, 1 part, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, etc.

[0060] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.

[0061] It is understandable that phosphorus-based flame retardants decompose to form a non-flammable liquid film of phosphoric acid during combustion. At the same time, phosphoric acid is further dehydrated to form metaphosphoric acid, which is further polymerized to form polymetaphosphoric acid. In this process, not only does the covering layer generated by phosphoric acid have a covering effect, but also because the generated polymetaphosphoric acid is a strong acid and a strong dehydrating agent, it dehydrates the polymer and carbonizes it, changing the mode of the polymer combustion process and forming a carbon film on its surface to isolate the air, thereby exerting a stronger flame retardant effect. At the same time, phosphorus-based flame retardants are also a free radical scavenger. Using mass spectrometry technology, it is found that any phosphorus-containing compound forms PO· when the polymer burns. It can combine with hydrogen atoms in the flame area to suppress the flame. In addition, the moisture produced by phosphorus-based flame retardants during the flame retardant process can, on the one hand, reduce the temperature of the condensed phase, and on the other hand, dilute the concentration of combustibles in the gas phase, thereby better playing a flame retardant role. Nitrogen-based flame retardants decompose at high temperatures to produce non-combustible gases such as ammonia, water vapor, and nitrogen. These gases can dilute the concentration of combustibles in the gas phase and inhibit combustion. The two work synergistically in the condensed phase and gas phase to increase the carbonization rate, form a more stable and uniform carbon layer, and improve the flame retardant effect. B in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital that can accept lone pairs of electrons and can produce a synergistic effect when coordinated with phosphorus, thereby improving the flame retardant effect. In addition, boron forms boric acid during the combustion process, and boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer, which isolates the release of combustible gases and the entry of external heat into the interior; the ring structure R2 with a carbon-hydrogen ratio greater than 1 has a higher carbon-hydrogen ratio, and the benzofuran group and polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. The modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant contain a large amount of silicon and oxygen elements. During the combustion process of the polymer, they form phosphates with the acidic gas after the combustion of the phosphorus-based flame retardant, promote the reaction of the phosphorus element with the polymer, and thus quickly form a carbon layer. The SiO2 generated after the combustion of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant is interspersed in the coke layer, similar to the role of sand in cement, making the coke layer more stable. The coke layer makes it difficult for heat to penetrate the condensed phase, preventing oxygen from entering the combustion area and the gaseous or liquid products generated by degradation from overflowing the surface of the material.The boron in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has an empty 2Pz orbital that can accept lone pairs of electrons and produce a synergistic effect when coordinated with phosphorus. The synergistic effect of boron and phosphorus makes the above reaction faster. At the same time, the combustion of nitrogen flame retardants produces a large amount of non-combustible gas, which causes the system in the molten state of the incompletely carbonized part of TPV to foam, causing the burning polymer to produce a large number of pores. At the same time, the organic matter continues to react, dehydrate and carbonize to form inorganic matter and carbon residues. When the reaction is completed, the system gels and solidifies, and finally forms a porous foam carbon layer.

[0062] The thermoplastic vulcanized rubber material of the invention comprises ethylene propylene diene monomer rubber, polypropylene, phosphorus-based flame retardant, nitrogen-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, and crosslinking agent. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the phosphorus flame retardant providing the acid source and the nitrogen flame retardant providing the gas source to synergistically flame retard, thereby reducing the amount of the flame retardant and improving the flame retardant properties and mechanical properties of the thermoplastic vulcanized rubber material. The thermoplastic vulcanized rubber material provided by the present invention has excellent flame retardant properties.

[0063] In some embodiments, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.

[0064] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.

[0065] In some embodiments, R2 is a benzofuranyl group.

[0066] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.

[0067] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.

[0068] In some embodiments, R2 is a naphthyl ring group.

[0069] In some embodiments, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

[0070]

[0071] In some embodiments, the molar ratio of compound 1 to compound 2 during the above reaction is 2:1.

[0072] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.

[0073] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.

[0074] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.

[0075] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.

[0076] In some embodiments, compound 2 is dibenzofuran-4-boronic acid.

[0077] In some embodiments, the structural formula of compound 3 is:

[0078]

[0079] The following is designated as modified POSS flame retardant synergist 1.

[0080] In some embodiments, the structural formula of compound 3 is:

[0081]

[0082] The following is designated as modified POSS flame retardant synergist 2.

[0083] In some embodiments, the preparation method of compound 3 comprises the following steps:

[0084] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;

[0085] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;

[0086] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

[0087] In some embodiments, the catalyst is acetic acid.

[0088] In some embodiments, the solvent is ethanol.

[0089] In some embodiments, the raw materials of the thermoplastic vulcanizate material include, by weight:

[0090] 50-70 parts of EPDM rubber,

[0091] Polypropylene 10-30 parts

[0092] Phosphorus flame retardant 20-30 parts,

[0093] 20-30 parts of nitrogen flame retardant,

[0094] 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,

[0095] Cross-linking agent 0.5-4 parts.

[0096] It can be understood that reducing the amount of phosphorus-based flame retardant, nitrogen-based flame retardant and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist can further improve the mechanical properties of the thermoplastic vulcanizate rubber material.

[0097] It is understandable that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist has two inorganic silicon cage cores, and the polypropylene macromolecule can be inserted into the inorganic silicon cage core structure to form a more stable molecular structure, so the anti-cracking performance of TPV materials will be significantly improved. The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains amine polar groups, which can be more conducive to the dispersion of flame retardants and also improve the anti-cracking performance of TPV materials.

[0098] In some embodiments, the phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide flame retardant;

[0099] And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

[0100] It is understood that the phosphorus-based flame retardants include, but are not limited to, aluminum hypophosphite, calcium hypophosphite, diethyl aluminum hypophosphite, methylethyl aluminum hypophosphite and phenyl aluminum hypophosphite.

[0101] In some embodiments, the phosphorus-based flame retardant is diethyl aluminum phosphite.

[0102] In some embodiments, the nitrogen-based flame retardant is melamine urate.

[0103] In some embodiments, the crosslinking agent includes but is not limited to peroxide crosslinking agents and phenolic resin crosslinking agents. Peroxide crosslinking agents include but are not limited to benzoyl peroxide (BPO), dicumyl peroxide (DCP), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (curing agent bis-25).

[0104] In some embodiments, the raw materials of the thermoplastic vulcanized rubber material also include at least one of a plasticizer, a lubricant, an antioxidant, a toughening agent, a compatibilizer, and a filler; wherein the raw materials are calculated in parts by weight, the plasticizer is 20-40 parts, the lubricant is 0.2-1 parts, the antioxidant is 0.5-2 parts, the toughening agent is 5-10 parts, the compatibilizer is 5-10 parts, and the filler is 5-10 parts.

[0105] In some embodiments, the plasticizer includes, but is not limited to, phthalates, fatty dibasic acid esters, fatty acid esters, phosphate esters, polyesters, epoxies, and paraffin oils. Phthalate plasticizers include but are not limited to dibutyl phthalate (DBP) and dioctyl phthalate (DOP). Such plasticizers can improve the flexibility, adhesion and low temperature resistance of the rubber compound; fatty dibasic acid ester plasticizers include but are not limited to dioctyl adipate (DOA), dioctyl azelaic acid (DOZ) and dioctyl sebacate (DOS). Such plasticizers have excellent cold resistance; fatty acid ester plasticizers include but are not limited to oleic acid esters, pentaerythritol fatty acid esters, and citrates. Such plasticizers have excellent cold resistance and water resistance; phosphate ester plasticizers include but are not limited to tricresyl phosphate (TCP) and trioctyl phosphate (TOP). Such plasticizers are mainly used to improve flame resistance; epoxy plasticizers include but are not limited to epoxidized oils, epoxidized fatty acid monoesters and epoxidized tetrahydrophthalates. Such plasticizers have good heat resistance and light resistance; paraffin oil is mainly used to reduce hardness. The types of plasticizers are not limited herein, and those skilled in the art can select plasticizers according to the specific application needs and performance requirements of TPV to achieve the purpose of improving processing performance, reducing hardness, and improving cold resistance, oil resistance or flame resistance.

[0106] In some embodiments, the antioxidant includes but is not limited to asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants. Hindered phenol antioxidants include but are not limited to antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), BHT (2,6-di-tert-butyl-p-cresol), antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate); aromatic amine antioxidants include but are not limited to diphenylamine, p-phenylenediamine and dihydroquinoline and its derivatives or polymers, such as antioxidant 445 (4,4'-bis(α.α- The antioxidants include, but are not limited to, dimethylbenzyl)diphenylamine); thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearate thiodipropionate), and DSTP (octadecyl thiodipropionate); phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol diphosphite distearyl), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite). By adding antioxidants, the antioxidant properties and aging resistance of polymer materials are beneficial, and the service life of polymer materials is extended. The types of antioxidants are not limited here, and those skilled in the art can choose according to actual needs.

[0107] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding a lubricant, it is beneficial to promote the mixing of various raw materials to be more uniform, while improving the fluidity of the polymer resin, reducing the friction coefficient, making the surface of the product smoother, improving processing efficiency, and improving the transparency and gloss of the plastic. The type of lubricant is not limited here, and those skilled in the art can select it according to actual needs.

[0108] In some embodiments, the toughening agent includes vinyl polymer grafted polyether polyol (POP), polyolefin elastomer (POE), olefin block copolymer (OBC), ethylene-vinyl acetate copolymer (EVA), and the like.

[0109] In some embodiments, the compatibilizer is one or more of PE grafted maleic anhydride, EPDM grafted maleic anhydride, EVA grafted maleic anhydride, preferably polypropylene grafted maleic anhydride (PP-g-MAH). PP-g-MAH can be used to improve the compatibility of the flame retardant with the matrix material because it contains both non-polar PP segments and polar maleic anhydride segments. Preferably, the PP-g-MAH has a grafting rate of 1.2% and a melt index (230°C, 2.16Kg) greater than 50g / 10min.

[0110] In some embodiments, the filler includes, but is not limited to, calcium carbonate (CaCO3), talc, wollastonite, kaolin, white carbon, and barium sulfate.

[0111] In a second aspect of the present invention, there is provided a method for preparing the above-mentioned thermoplastic vulcanized rubber material, comprising the following steps:

[0112] The raw materials, including EPDM rubber, polypropylene, phosphorus-based flame retardant, nitrogen-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, are mixed in an internal mixer according to weight to form a colloid, and the colloid is cooled and crushed to obtain crushed rubber blocks;

[0113] The broken rubber blocks and the cross-linking agent are mixed uniformly, melt-blended in an extruder, dynamically vulcanized, extruded and water-cooled to obtain granular material, namely the thermoplastic vulcanized rubber material.

[0114] In some embodiments, the raw material further comprises at least one of a plasticizer, a lubricant, an antioxidant, a toughening agent, a compatibilizer, and a filler;

[0115] And / or, the processing temperature of each temperature zone of the extruder is: 90-100°C in zone 1, 160-180°C in zone 2, 190-200°C in zone 3, 190-220°C in zone 4, 190-220°C in zone 5, 190-220°C in zone 6, 190-220°C in zone 7, 190-220°C in zone 8, 180-200°C in zone 9, 180-200°C in zone 10, 200-210°C in zone 11, die head 200-210°C, main engine speed 400-600r / min, feed speed 30-60r / min. The content of the present invention is explained below through specific examples and data. The information of the raw materials involved in the specific implementation method is shown in Table 1:

[0116] Table 1 Information of raw materials of Examples and Comparative Examples

[0117]

[0118]

[0119] Preparation method of modified POSS flame retardant synergist 1

[0120] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 1.

[0121] Preparation method of modified POSS flame retardant synergist 2

[0122] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain dibenzofuran-3-boric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 2.

[0123] Preparation method of modified POSS flame retardant synergist 3

[0124] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain methylboric acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 3.

[0125] Preparation method of modified POSS flame retardant synergist 4

[0126] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 mL of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain phenylboronic acid-modified aminopropyl heptaisobutyl caged polysilsesquioxane, i.e., modified POSS flame retardant synergist 4.

[0127] Embodiment 1:

[0128] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0129] 50 parts of EPDM rubber;

[0130] Polypropylene 10 parts;

[0131] 40 parts of diethyl aluminum hypophosphite;

[0132] 40 parts of melamine urate;

[0133] 110 parts of modified POSS flame retardant synergist;

[0134] 0.5 parts of benzoyl peroxide;

[0135] 80 parts of paraffin oil;

[0136] 0.5 part of silicone;

[0137] Antioxidant 10100.5 parts;

[0138] POE81505 copies;

[0139] Maleic anhydride grafted polypropylene 5 parts;

[0140] 10 parts of talcum powder;

[0141] The preparation method is:

[0142] EPDM rubber, polypropylene, diethyl aluminum hypophosphite, melamine urate, modified POSS flame retardant synergist 1, paraffin oil, silicone, antioxidant 1010, POE8150, maleic anhydride grafted polypropylene, and talcum powder are mixed into a colloid in an internal mixer according to the above weight parts, and the colloid is cooled and crushed to obtain crushed rubber blocks;

[0143] The crushed rubber block is uniformly mixed with the above-mentioned weight portion of benzoyl peroxide, and the pellets, i.e., thermoplastic vulcanized rubber material, are obtained by melt blending, dynamic vulcanization, extrusion and water-cooling granulation through a high-torque twin-screw extruder; wherein the processing temperatures of each temperature zone of the high-torque twin-screw extruder are: 90-100° C. in zone 1, 160-180° C. in zone 2, 190-200° C. in zone 3, 190-220° C. in zone 4, 190-220° C. in zone 5, 190-220° C. in zone 6, 190-220° C. in zone 7, 190-220° C. in zone 8, 180-200° C. in zone 9, 180-200° C. in zone 10, 200-210° C. in zone 11, and 200-210° C. at the die head, 400-600 r / min at the main engine speed, and 30-60 r / min at the feeding speed.

[0144] Embodiment 2:

[0145] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0146] EPDM rubber 70 parts;

[0147] Polypropylene 5 parts;

[0148] 20 parts of diethyl aluminum hypophosphite;

[0149] 20 parts of melamine urate;

[0150] 115 parts of modified POSS flame retardant synergist;

[0151] 4 parts of benzoyl peroxide;

[0152] 80 parts of paraffin oil;

[0153] 0.5 part of silicone;

[0154] Antioxidant 10100.5 parts;

[0155] POE81505 copies;

[0156] Maleic anhydride grafted polypropylene 5 parts;

[0157] 10 parts of talcum powder;

[0158] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0159] Embodiment 3:

[0160] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0161] 60 parts of EPDM rubber;

[0162] Polypropylene 18 parts;

[0163] 30 parts of diethyl aluminum hypophosphite;

[0164] 30 parts of melamine urate;

[0165] 12 parts of modified POSS flame retardant synergist;

[0166] 2.5 parts of benzoyl peroxide;

[0167] 80 parts of paraffin oil;

[0168] 0.5 part of silicone;

[0169] Antioxidant 10100.5 parts;

[0170] POE81505 copies;

[0171] Maleic anhydride grafted polypropylene 5 parts;

[0172] 10 parts of talcum powder;

[0173] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0174] Embodiment 4:

[0175] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0176] 60 parts of EPDM rubber;

[0177] Polypropylene 30 parts;

[0178] 20 parts of diethyl aluminum hypophosphite;

[0179] 40 parts of melamine urate;

[0180] 110 parts of modified POSS flame retardant synergist;

[0181] 0.5 parts of benzoyl peroxide;

[0182] 80 parts of paraffin oil;

[0183] 0.5 part of silicone;

[0184] Antioxidant 10100.5 parts;

[0185] POE81505 copies;

[0186] Maleic anhydride grafted polypropylene 5 parts;

[0187] 10 parts of talcum powder;

[0188] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0189] Embodiment 5:

[0190] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0191] 50 parts of EPDM rubber;

[0192] Polypropylene 10 parts;

[0193] 30 parts of diethyl aluminum hypophosphite;

[0194] 30 parts of melamine urate;

[0195] 18 parts of modified POSS flame retardant synergist;

[0196] 0.5 parts of benzoyl peroxide;

[0197] 80 parts of paraffin oil;

[0198] 0.5 part of silicone;

[0199] Antioxidant 10100.5 parts;

[0200] POE81505 copies;

[0201] Maleic anhydride grafted polypropylene 5 parts;

[0202] 10 parts of talcum powder;

[0203] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0204] Embodiment 6:

[0205] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0206] EPDM rubber 70 parts;

[0207] Polypropylene 30 parts;

[0208] 30 parts of diethyl aluminum hypophosphite;

[0209] 30 parts of melamine urate;

[0210] 18 parts of modified POSS flame retardant synergist;

[0211] 0.5 parts of benzoyl peroxide;

[0212] 80 parts of paraffin oil;

[0213] 0.5 part of silicone;

[0214] Antioxidant 10100.5 parts;

[0215] POE81505 copies;

[0216] Maleic anhydride grafted polypropylene 5 parts;

[0217] 10 parts of talcum powder;

[0218] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0219] Embodiment 7:

[0220] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0221] 60 parts of EPDM rubber;

[0222] Polypropylene 18 parts;

[0223] 25 parts of diethyl aluminum hypophosphite;

[0224] 25 parts of melamine urate;

[0225] 18 parts of modified POSS flame retardant synergist;

[0226] 0.5 parts of benzoyl peroxide;

[0227] 80 parts of paraffin oil;

[0228] 0.5 part of silicone;

[0229] Antioxidant 10100.5 parts;

[0230] POE81505 copies;

[0231] Maleic anhydride grafted polypropylene 5 parts;

[0232] 10 parts of talcum powder;

[0233] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0234] Embodiment 8:

[0235] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0236] 60 parts of EPDM rubber;

[0237] Polypropylene 18 parts;

[0238] 25 parts of diethyl aluminum hypophosphite;

[0239] 25 parts of melamine urate;

[0240] 28 parts of modified POSS flame retardant synergist;

[0241] 0.5 parts of benzoyl peroxide;

[0242] 80 parts of paraffin oil;

[0243] 0.5 part of silicone;

[0244] Antioxidant 10100.5 parts;

[0245] POE81505 copies;

[0246] Maleic anhydride grafted polypropylene 5 parts;

[0247] 10 parts of talcum powder;

[0248] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0249] Embodiment 9:

[0250] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0251] 60 parts of EPDM rubber;

[0252] Polypropylene 18 parts;

[0253] 25 parts of diethyl aluminum hypophosphite;

[0254] 25 parts of melamine urate;

[0255] 18 parts of modified POSS flame retardant synergist;

[0256] 0.5 parts of benzoyl peroxide;

[0257] 80 parts of paraffin oil;

[0258] Silicone 0.2 parts;

[0259] 10102 parts of antioxidant;

[0260] POE81505 copies;

[0261] Maleic anhydride grafted polypropylene 10 parts;

[0262] 5 parts of talcum powder;

[0263] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0264] Embodiment 10:

[0265] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0266] 60 parts of EPDM rubber;

[0267] Polypropylene 18 parts;

[0268] 25 parts of diethyl aluminum hypophosphite;

[0269] 25 parts of melamine urate;

[0270] 18 parts of modified POSS flame retardant synergist;

[0271] 0.5 parts of benzoyl peroxide;

[0272] 50 parts of paraffin oil;

[0273] 1 part silicone;

[0274] Antioxidant 10100.5 parts;

[0275] POE81508 copies;

[0276] Maleic anhydride grafted polypropylene 5 parts;

[0277] 10 parts of talcum powder;

[0278] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0279] Embodiment 11:

[0280] Please refer to Table 1 and Table 2. This example includes the following raw materials in parts by weight:

[0281] 60 parts of EPDM rubber;

[0282] Polypropylene 18 parts;

[0283] 25 parts of diethyl aluminum hypophosphite;

[0284] 25 parts of melamine urate;

[0285] 18 parts of modified POSS flame retardant synergist;

[0286] 0.5 parts of benzoyl peroxide;

[0287] 100 parts of paraffin oil;

[0288] Silicone 0.6 part;

[0289] Antioxidant 10101.2 parts;

[0290] POE815010 copies;

[0291] Maleic anhydride grafted polypropylene 8 parts;

[0292] 7 parts of talcum powder;

[0293] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0294] Comparative Example 1:

[0295] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0296] 60 parts of EPDM rubber;

[0297] Polypropylene 18 parts;

[0298] 15 parts of diethyl aluminum hypophosphite;

[0299] 25 parts of melamine urate;

[0300] 118 parts of modified POSS flame retardant synergist;

[0301] 0.5 parts of benzoyl peroxide;

[0302] 80 parts of paraffin oil;

[0303] 0.5 part of silicone;

[0304] Antioxidant 10100.5 parts;

[0305] POE81505 copies;

[0306] Maleic anhydride grafted polypropylene 5 parts;

[0307] 10 parts of talcum powder;

[0308] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0309] Comparative Example 2:

[0310] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0311] 60 parts of EPDM rubber;

[0312] Polypropylene 18 parts;

[0313] 33 parts of diethyl aluminum hypophosphite;

[0314] 25 parts of melamine urate;

[0315] 0.5 parts of benzoyl peroxide;

[0316] 80 parts of paraffin oil;

[0317] 0.5 part of silicone;

[0318] Antioxidant 10100.5 parts;

[0319] POE81505 copies;

[0320] Maleic anhydride grafted polypropylene 5 parts;

[0321] 10 parts of talcum powder;

[0322] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0323] Comparative Example 3:

[0324] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0325] 60 parts of EPDM rubber;

[0326] Polypropylene 18 parts;

[0327] 50 parts of melamine urate;

[0328] 18 parts of modified POSS flame retardant synergist;

[0329] 0.5 parts of benzoyl peroxide;

[0330] 80 parts of paraffin oil;

[0331] 0.5 part of silicone;

[0332] Antioxidant 10100.5 parts;

[0333] POE81505 copies;

[0334] Maleic anhydride grafted polypropylene 5 parts;

[0335] 10 parts of talcum powder;

[0336] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0337] Comparative Example 4:

[0338] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0339] 60 parts of EPDM rubber;

[0340] Polypropylene 18 parts;

[0341] 50 parts of diethyl aluminum hypophosphite;

[0342] 18 parts of modified POSS flame retardant synergist;

[0343] 0.5 parts of benzoyl peroxide;

[0344] 80 parts of paraffin oil;

[0345] 0.5 part of silicone;

[0346] Antioxidant 10100.5 parts;

[0347] POE81505 copies;

[0348] Maleic anhydride grafted polypropylene 5 parts;

[0349] 10 parts of talcum powder;

[0350] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0351] Comparative Example 5:

[0352] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0353] 60 parts of EPDM rubber;

[0354] Polypropylene 18 parts;

[0355] 158 parts of modified POSS flame retardant synergist;

[0356] 0.5 parts of benzoyl peroxide;

[0357] 80 parts of paraffin oil;

[0358] 0.5 part of silicone;

[0359] Antioxidant 10100.5 parts;

[0360] POE81505 copies;

[0361] Maleic anhydride grafted polypropylene 5 parts;

[0362] 10 parts of talcum powder;

[0363] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0364] Comparative Example 6:

[0365] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0366] 60 parts of EPDM rubber;

[0367] Polypropylene 18 parts;

[0368] 58 parts of diethyl aluminum hypophosphite;

[0369] 0.5 parts of benzoyl peroxide;

[0370] 80 parts of paraffin oil;

[0371] 0.5 part of silicone;

[0372] Antioxidant 10100.5 parts;

[0373] POE81505 copies;

[0374] Maleic anhydride grafted polypropylene 5 parts;

[0375] 10 parts of talcum powder;

[0376] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0377] Comparative Example 7:

[0378] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0379] 60 parts of EPDM rubber;

[0380] Polypropylene 18 parts;

[0381] 58 parts of melamine urate;

[0382] 0.5 parts of benzoyl peroxide;

[0383] 80 parts of paraffin oil;

[0384] 0.5 part of silicone;

[0385] Antioxidant 10100.5 parts;

[0386] POE81505 copies;

[0387] Maleic anhydride grafted polypropylene 5 parts;

[0388] 10 parts of talcum powder;

[0389] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0390] Comparative Example 8:

[0391] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0392] 60 parts of EPDM rubber;

[0393] Polypropylene 18 parts;

[0394] 25 parts of diethyl aluminum hypophosphite;

[0395] 25 parts of melamine urate;

[0396] 8 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;

[0397] 0.5 parts of benzoyl peroxide;

[0398] 80 parts of paraffin oil;

[0399] 0.5 part of silicone;

[0400] Antioxidant 10100.5 parts;

[0401] POE81505 copies;

[0402] Maleic anhydride grafted polypropylene 5 parts;

[0403] 10 parts of talcum powder;

[0404] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0405] Comparative Example 9:

[0406] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0407] 60 parts of EPDM rubber;

[0408] Polypropylene 18 parts;

[0409] 25 parts of diethyl aluminum hypophosphite;

[0410] 25 parts of melamine urate;

[0411] 8 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;

[0412] 0.5 parts of benzoyl peroxide;

[0413] 80 parts of paraffin oil;

[0414] 0.5 part of silicone;

[0415] Antioxidant 10100.5 parts;

[0416] POE81505 copies;

[0417] Maleic anhydride grafted polypropylene 5 parts;

[0418] 10 parts of talcum powder;

[0419] The preparation method is basically the same as that of Example 1, except that the ingredients and quantities of the raw material components are different, see Table 1 and Table 2.

[0420] Comparative Example 10:

[0421] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0422] 60 parts of EPDM rubber;

[0423] Polypropylene 18 parts;

[0424] 25 parts of diethyl aluminum hypophosphite;

[0425] 25 parts of melamine urate;

[0426] 2.6 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid;

[0427] 5.4 parts of aminopropyl heptaisobutyl caged polysilsesquioxane;

[0428] 0.5 parts of benzoyl peroxide;

[0429] 80 parts of paraffin oil;

[0430] 0.5 part of silicone;

[0431] Antioxidant 10100.5 parts;

[0432] POE81505 copies;

[0433] Maleic anhydride grafted polypropylene 5 parts;

[0434] 10 parts of talcum powder;

[0435] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0436] Comparative Example 11:

[0437] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0438] 60 parts of EPDM rubber;

[0439] Polypropylene 18 parts;

[0440] 25 parts of diethyl aluminum hypophosphite;

[0441] 25 parts of melamine urate;

[0442] 38 parts of modified POSS flame retardant synergist;

[0443] 0.5 parts of benzoyl peroxide;

[0444] 80 parts of paraffin oil;

[0445] 0.5 part of silicone;

[0446] Antioxidant 10100.5 parts;

[0447] POE81505 copies;

[0448] Maleic anhydride grafted polypropylene 5 parts;

[0449] 10 parts of talcum powder;

[0450] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0451] Comparative Example 12:

[0452] Please refer to Table 1 and Table 2. This comparative example includes the following raw materials in parts by weight:

[0453] 60 parts of EPDM rubber;

[0454] Polypropylene 18 parts;

[0455] 25 parts of diethyl aluminum hypophosphite;

[0456] 25 parts of melamine urate;

[0457] 48 parts of modified POSS flame retardant synergist;

[0458] 0.5 parts of benzoyl peroxide;

[0459] 80 parts of paraffin oil;

[0460] 0.5 part of silicone;

[0461] Antioxidant 10100.5 parts;

[0462] POE81505 copies;

[0463] Maleic anhydride grafted polypropylene 5 parts;

[0464] 10 parts of talcum powder;

[0465] The preparation method is basically the same as that of Example 1, except that the ingredients and portions of the raw material components are different, see Table 1 and Table 2.

[0466] The thermoplastic vulcanized rubber materials obtained in the above embodiments and comparative examples were injection molded or molded, and flame retardant grade, oxygen index, tensile strength, elongation at break, trouser tear, 110°C heat shock, 130°C heat shock, 150°C heat shock tests were performed. The test standards are as follows:

[0467] (1) Flame retardant grade

[0468] The test was conducted according to the UL94 standard, with a sample thickness of 3 mm and a test temperature of 23 ± 2 ° C. Three samples were tested using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd., and any dripping was observed.

[0469] (2) Oxygen index

[0470] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The oxygen index of three samples is tested using the oxygen index tester device of Fangshang Analytical Instrument Equipment Factory, Jiangning District, Nanjing, and the results are averaged.

[0471] (3) Tensile strength and elongation at break

[0472] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength and elongation at break of three specimens were tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.

[0473] (4) Trouser-shaped tear

[0474] The test was conducted in accordance with GB 16578.1-2008, with a test temperature of 23±2°C and a tensile speed of 250 mm / min. The trouser tear strength of three samples was tested using a micro-controlled electronic universal material tensile testing machine from Dongguan High Speed ​​Rail Testing Co., Ltd., and the average result was taken.

[0475] (5) 110-150℃ thermal shock

[0476] The test was carried out in accordance with Appendix A of GB / T 32129-2015, with a test temperature of 23±2°C and a weight of 2kg. Using the heat shock test device of Hebei Zhongke Beigong Testing Instrument Co., Ltd., three samples were tested at each temperature, and the results were averaged.

[0477] The test results are shown in Table 3.

[0478] Table 2 Examples of the present invention and comparative examples

[0479]

[0480]

[0481]

[0482]

[0483]

[0484] Table 3 Performance test table of the embodiments of the present invention and comparative examples

[0485]

[0486]

[0487] According to Table 3, it can be seen that the flame retardant properties of the TPV injection molded sheets of Examples 1-11 are good, and the flame retardant grades all reach V0 level. When the V0 level is tested, no dripping occurs, and the oxygen index is ≥29%, which indicates that the TPV material of the present invention has good flame retardant properties. It can be seen from Example 5 and Example 1 that by further reducing the amount of phosphorus-based flame retardant diethyl aluminum hypophosphite, nitrogen-based flame retardant melamine urate, and modified POSS flame retardant synergist 1, the tensile strength, elongation at break, trouser tear, and 110-150°C thermal shock of the TPV injection molded sheet are all improved, which indicates that further reducing the amount of phosphorus-based flame retardant, nitrogen-based flame retardant, and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist can improve the mechanical properties of the TPV material. It can be seen from Example 7 and Comparative Example 1 that the number of modified POSS flame retardant synergist 1 is too high, the flame retardant grade is V1, the flame retardant performance is not up to standard, and the oxygen index decreases; it can be seen from Example 7 and Comparative Example 2 that when the modified POSS flame retardant synergist 1 is not added, there are drips, the oxygen index decreases, and the tensile strength, elongation at break and trouser-shaped tear are all reduced; it can be seen from Example 7 and Comparative Example 3 that when the phosphorus-based flame retardant diethyl aluminum hypophosphite is not added, the flame retardant grade is V2, there are drips, the flame retardant performance is not up to standard, and the oxygen index decreases; it can be seen from Example 7 and Comparative Example 4 that when the nitrogen-based flame retardant melamine urate (MCA) is not added, the flame retardant grade is V1, the flame retardant performance is not up to standard, the oxygen index decreases, and the tensile strength, elongation at break and trouser-shaped tear as well as 110-150°C thermal shock are all reduced; it can be seen from Example 7 and Comparative Example 5 that only the When modified POSS flame retardant synergist 1 is used as a flame retardant, the flame retardant grade is V2, the flame retardant performance is not up to standard, the oxygen index is reduced, and the elongation at break is reduced; it can be seen from Example 7 and Comparative Example 6 that when only the phosphorus-based flame retardant diethyl aluminum hypophosphite is used, the flame retardant grade is V2, there are drippings, the flame retardant performance is not up to standard, the oxygen index is reduced, and the tensile strength, elongation at break, trouser tear and 110-150°C thermal shock are all reduced; it can be seen from Example 7 and Comparative Example 7 that when only the nitrogen-based flame retardant melamine urate (MCA) is used, the flame retardant grade is V2, there are drippings, the flame retardant performance is not up to standard, and the oxygen index is low, which shows that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists have a synergistic flame retardant effect with phosphorus-based flame retardants and nitrogen-based flame retardants, reducing the amount of various flame retardants while improving the flame retardant and mechanical properties of TPV materials.It can be seen from Example 7 and Comparative Example 8 that the modified POSS flame retardant synergist 1 is compared with the benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, and the anti-drip, oxygen index, elongation at break and trouser-shaped tear are all improved; it can be seen from Example 7 and Comparative Example 9 that the modified POSS flame retardant synergist 1 is compared with the aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, and the flame retardant grade, anti-drip, oxygen index, elongation at break and trouser-shaped tear are all improved; it can be seen from Example 7 and Comparative Example 10 that the modified POSS flame retardant synergist 1 is compared with the flame retardant mixed with aminopropyl heptaisobutyl caged polysilsesquioxane and benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid, and the anti-drip The dripping performance, oxygen index, tensile strength, elongation at break and trouser-shaped tear are all improved; it can be seen from Example 7 and Comparative Example 11 that the flame retardant grade, anti-dripping and oxygen index of the modified POSS flame retardant synergist 1 are improved compared with the modified POSS flame retardant 3, i.e., the methyl boric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant; it can be seen from Example 7 and Comparative Example 12 that the anti-dripping performance, oxygen index and trouser-shaped tear of the modified POSS flame retardant synergist 1 are improved compared with the modified POSS flame retardant 4, i.e., the phenyl boric acid modified aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, which illustrates that the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists of the present invention have excellent flame retardant properties.

[0488] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A thermoplastic vulcanized rubber material, characterized in that: The raw materials of the thermoplastic vulcanized rubber material include, by weight: 50-70 parts of EPDM rubber, Polypropylene 5-30 parts Phosphorus flame retardant 20-40 parts, 20-40 parts of nitrogen flame retardant, 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Cross-linking agent 0.5-4 parts, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.

2. The thermoplastic vulcanized rubber material according to claim 1, characterized in that The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.

3. The thermoplastic vulcanized rubber material according to claim 1, characterized in that The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:

4. The thermoplastic vulcanized rubber material according to claim 3, characterized in that: The molar ratio of compound 1 to compound 2 is 2:

1.

5. The thermoplastic vulcanized rubber material according to claim 3, characterized in that: The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.

6. The thermoplastic vulcanizate according to claim 1, characterized in that: The raw materials of the thermoplastic vulcanized rubber material include, by weight: 50-70 parts of EPDM rubber, Polypropylene 10-30 parts Phosphorus flame retardant 20-30 parts, 20-30 parts of nitrogen flame retardant, 2-8 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Cross-linking agent 0.5-4 parts.

7. The thermoplastic vulcanizate according to claim 1, characterized in that: The phosphorus-based flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphorus oxide; And / or, the nitrogen-based flame retardant includes at least one of melamine urate, melamine phosphate, melamine inorganic acid salt, dicyandiamide, and melamine.

8. The thermoplastic vulcanizate according to claim 1, characterized in that: The raw materials of the thermoplastic vulcanized rubber material also include at least one of a plasticizer, a lubricant, an antioxidant, a toughening agent, a compatibilizer, and a filler; wherein the raw materials are calculated by weight: 20-40 parts of the plasticizer, 0.2-1 parts of the lubricant, 0.5-2 parts of the antioxidant, 5-10 parts of the toughening agent, 5-10 parts of the compatibilizer, and 5-10 parts of the filler.

9. A method for preparing a thermoplastic vulcanized rubber material as claimed in claim 1, characterized in that: The following steps are involved: The raw materials, including EPDM rubber, polypropylene, phosphorus-based flame retardant, nitrogen-based flame retardant, modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, are mixed in an internal mixer according to weight to form a colloid, and the colloid is cooled and crushed to obtain crushed rubber blocks; The broken rubber blocks and the cross-linking agent are mixed uniformly, melt-blended in an extruder, dynamically vulcanized, extruded and water-cooled to obtain granular material, namely the thermoplastic vulcanized rubber material.

10. The method for preparing a thermoplastic vulcanized rubber material according to claim 9, characterized in that: The raw materials also include at least one of a plasticizer, a lubricant, an antioxidant, a toughening agent, a compatibilizer, and a filler; And / or, the processing temperature of each temperature zone of the extruder is: 90-100°C in zone 1, 160-180°C in zone 2, 190-200°C in zone 3, 190-220°C in zone 4, 190-220°C in zone 5, 190-220°C in zone 6, 190-220°C in zone 7, 190-220°C in zone 8, 180-200°C in zone 9, 180-200°C in zone 10, 200-210°C in zone 11, 200-210°C in die head, 400-600r / min in main engine speed, and 30-60r / min in feeding speed.